THE COMPARATIVE STUDY BETWEEN READING STRATEGIES USED BY SUCCESSFUL AND UNSUCCESSFUL STUDENTS - Putri Amanda Gustiana; Rudi Afriazi; Hilda Puspita Puspita (Journal of English Education and Teaching, 2018)
The aim of this research was to find out the strategies used by the English Education Study Program students in learning reading skill. The research was designed as a comparative research. The population of the research was 74 students of English Education Study Program of Universitas Bengkulu in the 2015/2016 academic year. The samples were 74 students which consist of 59 successful students and 15 unsuccessful students, taken all of the total population. The data were collected by using a set of questionnaire and documentation. There were 45 statements of reading learning strategies which consisted of six categories of learning strategies proposed by Oxford (1990). They were Memory related, metacognitive strategy, cognitive strategy, compensation and social affective strategy. The instrument of this research was adopted from Tabehinejad (2015). Meanwhile  documentation  instrument was transcript score from the sixth semester English Education Study Program. The result of this study showed between unsuccessful and successful students of  English  Education  Study Program preferred to use all category of  that learning strategy. In addition, the most frequently used strategy group by unsuccessful students was social and cognitive strategy. Meanwhile successful students used strategy group was social strategy.